(untitled) (Medina-Te : Jurnal Studi Islam, 2026)
This article aims to compare the thoughts of Al-Ghazali and Buya Hamka on tazkiyatun nafs (purification of the soul) and identify the steps taken by both in forming a spiritually pure personality. This study uses a qualitative method with a comparative approach. Data collection techniques were carried out through a literature review of Al-Ghazali's major works, namely Ihya' Ulumuddin and Bidayatul Hidayah, as well as Buya Hamka's Tafsir Al-Azhar, supplemented with other supporting literature. Data analysis was carried out using a descriptive-qualitative approach to examine each figure's approach to the concept of spiritual purification. The results of the study show that Al-Ghazali describes three stages of tazkiyatun nafs: takhalli (emptying oneself of bad traits), tahalli (adorn oneself with good morals), and tajalli (witnessing the presence of Allah). Meanwhile, Buya Hamka offers five steps: befriending good people, using reason wisely, controlling desires and anger, thinking before acting, and knowing oneself. Although they have different approaches, both emphasise the importance of moral and spiritual dimensions in the process of purifying the soul.